Way Out of the Matrix - Subbotin, Alexander (Journal of Economic Sociology, 2020)
The feature of this review is to study the properties of modern communications and relations between humans and information. An American journalist and ex-editor of The New Republic, Franklin Foer studies the origins, present, and future of new media. Starting with the meaning of their own names, global network companies claim to everyone that they are ruling the world. Social networks and even search engines collect data with ease and impunity from unsuspecting users who voluntarily publish open access information about themselves. Then, after acquiring the information they need, corporations like Google, Facebook, and Amazon use algorithms to control the behavior of a large part of the world. The review highlights the most important topics of the book: the reasons for degradation of individual taste and thought, ways corporations can follow their clients, the crisis of book publishing and professional journalism, and the importance of privacy. Foer does not spread panic; rather, he explains to the reader what problems modern information society faces. One of the main difficulties is that search engines and social networks do not allow users to filter content (despite an abundance of it) according to users’ personal interests but instead organize the output of material according to internal algorithms. Perhaps we should turn to traditional ways of comprehending the world, such as reading paper books. The Internet itself as a means of communication is not the ultimate evil but the fact that it has been turned into the only way of communication means it is relied on too extensively. As a result, the book World Without Mind by Franklin Foer offers a way to “exit the matrix” of the digital age.